Impacts of MR spectroscopic imaging on glioma patient management. (May 2014) - Chronaiou, Ioanna; Stensjøen, Anne Line; Sjøbakk, Torill Eidhammer; Esmaeili, Morteza; Bathen, Tone Frost
Abstract Magnetic resonance (MR) modalities are routine imaging tools in the diagnosis and management of gliomas. MR spectroscopic imaging (MRSI), which relies on the metabolic characteristics of tissues, has been developed to accelerate the understanding of gliomas and to aid in effective clinical decision making and development of targeted therapies. In this review, the potentials and practical challenges to frequently use this technique in clinical management of gliomas are discussed. The applications of new biomarkers detectable by MRSI in differential glioma diagnosis, pre- and post-treatment evaluations, and neurosurgery are also addressed.